Whole exome sequencing for the identification of CYP3A7 variants associated with tacrolimus concentrations in kidney transplant patients. Issue 1 (December 2018) - Sohn, Minji; Kim, Myeong; Han, Nayoung; Kim, In-Wha; Gim, Jungsoo; Min, Sang-Il; Song, Eun; Kim, Yon; Jung, Hun; Shin, Young; Ha, Jongwon; Oh, Jung
Abstract The purpose of this study was to identify genotypes associated with dose-adjusted tacrolimus trough concentrations (C0 /D) in kidney transplant recipients using whole-exome sequencing (WES). This study included 147 patients administered tacrolimus, including seventy-five patients in the discovery set and seventy-two patients in the replication set. The patient genomes in the discovery set were sequenced using WES. Also, known tacrolimus pharmacokinetics-related intron variants were genotyped. Tacrolimus C0 /D was log-transformed. Sixteen variants were identified including novelCYP3A7 rs12360 and rs10211 by ANOVA.CYP3A7 rs2257401 was found to be the most significant variant among the periods by ANOVA. Seven variants includingCYP3A7 rs2257401, rs12360, and rs10211 were analyzed by SNaPshot in the replication set and the effects on tacrolimus C0 /D were verified. A linear mixed model (LMM) was further performed to account for the effects of the variants and clinical factors. The combined set LMM showed that onlyCYP3A7 rs2257401 was associated with tacrolimus C0 /D after adjusting for patient age, albumin, and creatinine. TheCYP3A7 rs2257401 genotype variant showed a significant difference on the tacrolimus C0 /D in those expressingCYP3A5, showing its own effect. The results suggest thatCYP3A7 rs2257401 may serve as a significant genetic marker for tacrolimus pharmacokinetics in kidney transplantation.